Glymphatic system and mild traumatic brain injury: a mini review - Miettinen, Pihla; Utz, Begüm; Bañuelos-Cabrera, Ivette; Golanov, Eugene; Lenzner, Ziv; Lara-Valderrábano, Leonardo; Välimaa, Lasse; Harel, Adrian (Frontiers in Neuroscience, 2025)
Since the discovery of the glymphatic system in 2012, research on this brain-wide fluid exchange pathway has focused on understanding its role in different neurological diseases. Mild traumatic brain injury (mTBI) is a prevalent, yet often undiagnosed, condition that increases the risk of developing debilitating neurodegenerative diseases. mTBI may lead to impaired glymphatic system function and, therefore, accumulation of metabolic waste in the brain. In this review, we summarize 24 studies (10 rodent, 13 human, 1 both) published during 2013–2025, reporting post-mTBI changes in the glymphatic system. According to pre-clinical models, potential post-mTBI drivers of glymphatic dysfunction include depolarization of aquaporin 4 water channels and sleep deprivation. In studies on humans, evidence is contradictory; some studies show reduced post-mTBI glymphatic activity, while others report increased activity. However, these studies used different patient populations, which were likely exposed to different mTBI types and post-injury time frames. Furthermore, studies on humans used non-invasive imaging techniques, which only indirectly measure glymphatic activity. Taken together, these inconsistencies point to major gaps in the field, highlighting the need for standardized injury classification and post-injury time frames, and more direct measurements of glymphatic activity in humans. Notably, sleep deprivation, post-concussive symptoms, and cognitive impairment have often been linked to post-injury glymphatic dysfunction. Nevertheless, to better understand mTBI implications on glymphatic system functioning, further research is needed. Such research could help develop novel diagnostics or treatment strategies for mTBI and potentially mitigate the long-term risks of developing neurodegenerative disorders.